Obesity and menopause - Santiago Palacios; Peter Chedraui; Rafael Sánchez-Borrego; Pluvio Coronado; Rossella E. Nappi (Gynecological Endocrinology, 2024)
Obesity is not a choice or a result of lack of willpower, but a multifactorial, chronic, progressive, and relapsing disease. During menopause, hormonal and body composition changes lead to greater visceral adiposity, that aggravates women’s health at a cardiometabolic, mechanic and mental level. Adiposity has been identified as an important modifier of reproductive hormones. During female midlife, obesity has been associated with menstrual cycle alterations (anovulatory cycles ending with abnormal bleedings), menopausal symptoms including hot flashes, poor quality of sleep, aches and joint pain, genitourinary symptoms, and reduced quality of life. However, the relationships between weight, the menopausal process, aging, and hormone levels remain poorly understood. Women with obesity have an increased risk of thromboembolic disease when using menopause hormone therapy (MHT), and it is probably the main medical condition to prescribe or not MHT. However, this risk depends on the route and type of MHT. The use of estrogen-only or combined transdermal MHT does not increase the risk of a thrombotic event in women with obesity.